Climate change and scenarios to guide regional adaptation plans for small scale farmers of Honduras - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Leader cocoa producers in Honduras and different Central American countries, members of ACICAFOC, gathered in Honduras in june 2015 to learn about climate change. They created regional adaptation plans based on Honduran socio-economic and climate scenarios that may affect their agricultural production. In 2014 UCI and CCAFS facilitated a Future Scenarios exercise with the SAG to strengthen the Agroclimatological Risk Management and Adaptation Strategy 2014-2024.